OBJEKTIFITAS DAN RASIONALITAS PENAFSIRAN AL-QUR’AN: PERSPEKTIF AL-JĀBIRĪ - Affandi, Abdullah (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Qur’anic Studies had been developed according to the changing times. Scholars have offered many different methods to reveal God’s messages in the Qur’an. Different methods and approaches were used by a number ofleading scholars. ‘Ābid al-Jābirī is among those leading scholars who focus on this study. In his works of Madkhal ilā al-Qur’ān and Fahm al-Qur’ān, al-Jābirī cultivates historically the Qur’anic discourse and interpretation and suggests a new method of understanding the Qur’an. Using a philosophical-historical approach, this paper examines the fundamental ideas of al-Jābirī in the Qur’anic discourse and in interpretation methodology.Keywords: Objektifikasi, Rasionalisasi, Tafsir al-Qur’an